Paf1C regulates RNA polymerase II progression by modulating elongation rate - Hou, Liming; Wang, Yating; Liu, Yu; Zhang, Nan; Shamovsky, Ilya; Nudler, Evgeny; Tian, Bin; Dynlacht, Brian David (Proceedings of the National Academy of Sciences - PNAS, 2019)
Elongation factor Paf1C regulates several stages of the RNA polymerase II (Pol II) transcription cycle, although it is unclear how it modulates Pol II distribution and progression in mammalian cells. We found that conditional ablation of Paf1 resulted in the accumulation of unphosphorylated and Ser5 phosphorylated Pol II around promoter-proximal regions and within the first 20 to 30 kb of gene bodies, respectively. Paf1 ablation did not impact the recruitment of other key elongation factors, namely, Spt5, Spt6, and the FACT complex, suggesting that Paf1 function may be mechanistically distinguishable from each of these factors. Moreover, loss of Paf1 triggered an increase in TSS-proximal nucleosome occupancy, which could impose a considerable barrier to Pol II elongation past TSS-proximal regions. Remarkably, accumulation of Ser5P in the first 20 to 30 kb coincided with reductions in histone H2B ubiquitylation within this region. Furthermore, we show that nascent RNA species accumulate within this window, suggesting a mechanism whereby Paf1 loss leads to aberrant, prematurely terminated transcripts and diminution of full-length transcripts. Importantly, we found that loss of Paf1 results in Pol II elongation rate defects with significant rate compression. Our findings suggest that Paf1C is critical for modulating Pol II elongation rates by functioning beyond the pause-release step as an “accelerator” over specific early gene body regions.